Release film for resin sheet molding

CN122996115APending Publication Date: 2026-10-27TOYOBO CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580022645.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-21
Filing Date
2025-03-12
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0016]另外,专利文献2的薄膜也同样地存在如下问题:突起的尺寸大,难以应对近年来的陶瓷生片厚度,另外,由于基材端部的突起个数多,因此在对该取出位置进行脱模涂布并使用其制作层叠陶瓷电容器时,其产品的不良率会变得比其他取出位置差

Benefits of technology

[0038]本发明的树脂片成型用脱模薄膜是在基材薄膜的一个面上具有脱模层、且控制了脱模层表面的突起个数和宽度方向上的突起的分布的脱模薄膜。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996115A_ABST
    Figure CN122996115A_ABST
Patent Text Reader

Abstract

The present invention provides a release film which can be peeled off with low and uniform force even for a thin ceramic green sheet, does not cause defects such as pinholes, and is excellent in smoothness. The present invention is a release film having a base material which is a polyester film having a width of 200 to 900 mm and a release layer, characterized in that, when wound in a roll shape, a range from one width direction end to a central direction 100 mm is set as R1, a range from the center to both width directions 50 mm is set as R2, a range from the other width direction end to the central direction 100 mm is set as R3, and the number of coarse projections of 500 nm or more present on the surface of each range R1, R2, R3 of the aforementioned release layer is respectively set as A1, A2, and A3, the coarse projection numbers indicated by A1, A2, and A3 are respectively 10 to 1000 / m 2 The coarse projection number ratio X calculated from X = ((A1 + A3) / 2) / A2 is 0.2 to 5.0.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a release film for molding resin sheets, and more specifically, to a release film used in molding thin resin sheets. Background Technology

[0002] Previously, release films with polyester film as the base material and a release layer laminated on it were used as engineering films for molding resin sheets such as adhesive sheets, cover films, polymer films, and optical lenses.

[0003] The aforementioned release film is also used as an engineering film for forming ceramic green sheets that require high smoothness, such as ceramic capacitors and ceramic substrates. In recent years, with the miniaturization and increasing capacitance of multilayer ceramic capacitors, there has been a trend towards thinner ceramic green sheets. Ceramic green sheets are formed by coating a slurry containing ceramic components such as barium titanate and binder resin onto a release film and then drying it. After printing electrodes on the formed ceramic green sheets and peeling them off from the release film, the ceramic green sheets are stacked, pressed, fired, and coated with external electrodes, thereby manufacturing multilayer ceramic capacitors.

[0004] When ceramic green sheets are formed on the surface of a release layer on a polyester film substrate, the wettability / smoothness of the release film when applying the ceramic slurry, and the peelability when peeling the ceramic green sheet from the release film, become increasingly important. If the smoothness is poor, problems such as pinholes, uneven thickness, and sheet defects may occur in the ceramic green sheets obtained after applying and drying the slurry.

[0005] In recent years, the advancement of thin-film ceramic green sheets has led to a demand for ceramic green sheets with a thickness of less than 1.0 μm, and more specifically, 0.2 μm to 1.0 μm. Consequently, the requirements for the smoothness of the release film have become increasingly stringent.

[0006] As a release film with excellent smoothness, Patent Document 1 discloses a release film characterized by having a number of protrusions larger than 1 μm of 1 per m. 2 A release layer is provided on the following film.

[0007] In addition, Patent Document 2 discloses an oriented polyester film roll that suppresses coating pinholes in the sheet formed on the surface of the release layer and has a good winding shape during winding.

[0008] In addition, document 3 discloses a method for manufacturing biaxially stretched polyester film, characterized in that transverse stretching is performed in a stenter oven where the number of dust particles is below a constant number.

[0009] Existing technical documents

[0010] Patent documents

[0011] Patent Document 1: Japanese Patent Application Publication No. 2007-237497

[0012] Patent Document 2: Japanese Patent Application Publication No. 2022-159254

[0013] Patent Document 3: Japanese Patent Application Publication No. 2009-012242 Summary of the Invention

[0014] The problem the invention aims to solve

[0015] However, the technology in Patent Document 1 is a technology for suppressing protrusions larger than 1 μm. For ceramic green sheets with a thickness of 0.2 μm to 1.0 μm that have been produced in recent years, it is necessary to suppress protrusions with a height lower than before.

[0016] Furthermore, the thin film in Patent Document 2 also suffers from the following problems: the protrusions are large, making it difficult to cope with the increasing thickness of ceramic green sheets in recent years; in addition, due to the large number of protrusions at the end of the substrate, the defect rate of products made from this extraction location during demolding coating and subsequent fabrication of multilayer ceramic capacitors becomes worse than that from other extraction locations. Additionally, there is the problem that powdery material from the ends accumulates in the cleanroom during demolding, leading to particle deterioration; this accumulation adheres during subsequent demolding processes.

[0017] In addition, cleaning of the biaxially stretched polyester film in Patent Document 3 inside and outside the coating machine and inside the tenter oven is essential. The film produced before cleaning has a large number of protrusions. Furthermore, the number of protrusions may fluctuate depending on the location, depending on the cleaning conditions.

[0018] Therefore, for ceramic green sheets with a thickness of approximately 0.2μm to 1.0μm manufactured in recent years, there is a need for technologies to further reduce the generation of pinholes. Furthermore, in order to further thin-filmize resin sheets such as ceramic green sheets, it is necessary to reduce the risk of pinhole generation. In addition, there is also a need to reduce the defect rate of resin sheets and decrease waste.

[0019] According to the research of the inventors, the number of protrusions on the surface of thin films produced using existing technology sometimes deviates in the width direction, and there are previously unnoticed conditions in order to suppress this deviation.

[0020] Therefore, the object of the present invention is to provide a release film that is not prone to defects in the entire width direction, even when a thin resin sheet or the like is molded.

[0021] Solution for solving the problem

[0022] In order to solve the above-mentioned problems, the inventors conducted in-depth research and found that if the release film described in this specification is used, the deviation in the width direction of the number of protrusions on the film surface can be suppressed, thus completing the present invention.

[0023] That is, the present invention comprises the following components. [1]

[0025] A release film has a substrate and a release layer, wherein the substrate is a polyester film with a width of 200-900 mm, and wherein...

[0026] R1 is defined as a 100mm area from one end in the width direction to the center when the roll is formed into a roll; R2 is defined as a 50mm area from the center to both sides in the width direction; R3 is defined as a 100mm area from the other end in the width direction to the center; and A1, A2, and A3 are defined as the number of coarse protrusions with a height of 500nm or more present on the surface of each of the aforementioned rolls R1, R2, and R3, as evaluated by the following method.

[0027] The number of coarse protrusions shown in A1, A2, and A3 are 10~1000 per m, respectively. 2 Scope

[0028] The ratio of coarse protrusions X calculated by X=((A1+A3) / 2) / A2 is 0.2~5.0.

[0029] (Evaluation method for the number of large protrusions)

[0030] A resin layer for evaluation is coated onto the surface of the aforementioned release layer to form a composition with a dried thickness of 500 nm and then dried. The positions of pinholes in the resulting resin layer are marked. The height of the protrusions is measured with the surface of the aforementioned resin layer as a reference. The protrusion height is obtained by adding the thickness of the aforementioned resin layer (500 nm) to the obtained protrusion height. The number of coarse protrusions with a protrusion height of 500 nm or more is measured. [2]

[0032] According to the release film described in [1], the average surface roughness (Sa) of the aforementioned release layer surface is less than 3.0 nm and the maximum protrusion height (Rp) is less than 200 nm. [3]

[0034] According to the release film described in [1] or [2], the thickness of the aforementioned release layer is less than 800 nm. [4]

[0036] The release film according to any one of [1] to [3], wherein the aforementioned release film is a release film for manufacturing ceramic green sheets or resin sheets.

[0037] The effects of the invention

[0038] The release film for resin sheet molding of the present invention is a release film having a release layer on one side of a substrate film, and controlling the number of protrusions on the surface of the release layer and the distribution of protrusions in the width direction.

[0039] The present invention provides a release film that can be defectively coated with resin sheets to form a slurry without deteriorating the rollability of the release film, and in particular, can defectively form ceramic green sheets. Attached Figure Description

[0040] Figure 1 This is a cross-sectional view schematically showing the height of the large protrusion in this invention. Detailed Implementation

[0041] The present invention will now be described in detail.

[0042] In this invention, by providing a release layer on one side of a substrate film with excellent smoothness, a release film with excellent smoothness, slurry coating properties, and peelability can be obtained.

[0043] There are no particular limitations on the release layer; silicone or resins containing long-chain alkyl groups can be used as release agents. By using these compositions to form the release layer, a release film with excellent peelability can be obtained.

[0044] (Polyester film)

[0045] The substrate film in this invention uses a polyester film with a width of 200-900 mm as the substrate. By using a polyester film with a width of 200-900 mm, a release film can be provided that more effectively controls the number of protrusions on the surface of the release layer and the distribution of protrusions in the width direction. Although a specific mechanism cannot be analyzed, the following tendency has been found: if the release film has a polyester film with a width of 200-900 mm, then when the release film is rolled into a roll (sometimes simply referred to as a release film roll), there is substantially no warping of the release film, the film thickness from one end of the release film to the other end is kept uniform, and the distribution of protrusions in the width direction can be uniformly controlled.

[0046] In one embodiment, a release layer can be processed on a polyester film with a width exceeding 900 mm, the film is cut within the scope of the present invention, and the cut release film is wound up.

[0047] On the other hand, if the film is wound up with the width of the substrate film significantly exceeding 900 mm, for example, air near the center may be difficult to expel during winding, and the film may move due to expansion and contraction caused by temperature changes, potentially resulting in protrusions caused by particle shedding or scratches from the substrate film.

[0048] As a result, when manufacturing raw sheets and resin sheets, the number of protrusions on the surface of the release layer and the distribution of protrusions in the width direction may deviate from the original design conditions.

[0049] Thus, by setting the width of the substrate film to 200-900 mm, the present invention enables the production of release films and release film rolls that more effectively control the number of protrusions on the surface of the release layer and the distribution of protrusions in the width direction. Furthermore, even during the storage period until the production of the green sheet, the number of protrusions on the surface of the release layer and the distribution of protrusions in the width direction can be well maintained, and the resin sheet can be coated to form a slurry without defects without deteriorating the rollability of the release film.

[0050] The polyester used to form the polyester film used as the substrate film (hereinafter referred to as the substrate) in this invention is not particularly limited, and any polyester commonly used as a substrate for release films can be used for film forming. Preferably, it is a crystalline linear saturated polyester formed from an aromatic dicarboxylic acid component and a glycol component, such as polyethylene terephthalate, polyethylene 2,6-naphthalenedicarboxylate, polyethylene butylene terephthalate, polyethylene terephthalate, or copolymers with components of these resins as the main components. Polyester films formed from polyethylene terephthalate are particularly preferred. In polyethylene terephthalate, the repeating unit of polyethylene terephthalate is preferably 90 mol% or more, more preferably 95 mol% or more, and small amounts of other dicarboxylic acid components and glycol components may also be copolymerized. For example, from a cost point of view, it is preferable to manufacture it only from terephthalic acid and ethylene glycol. Furthermore, known additives, such as antioxidants, light stabilizers, UV absorbers, and crystallizers, can be added to the extent that they do not impair the effect of the release film of the present invention. Considering the high biaxial elastic modulus, the polyester film is preferably a biaxially oriented polyester film.

[0051] The intrinsic viscosity of the aforementioned polyester film is preferably 0.50 to 0.70 dl / g, more preferably 0.52 to 0.62 dl / g. When the intrinsic viscosity is 0.50 dl / g or higher, significant breakage does not occur during the stretching process, which is preferable. Conversely, when the intrinsic viscosity is below 0.70 dl / g, the cutability is good when cutting to the specified product width, and dimensional defects are not produced, which is also preferable. Furthermore, the raw material granules are preferably thoroughly vacuum dried.

[0052] It should be noted that, in this specification, when referred to only as "polyester film", it refers to a polyester film having (layered) surface layer A and surface layer B.

[0053] The method for manufacturing the polyester film in this invention is not particularly limited, and conventionally used methods can be used. For example, the unstretched film can be obtained by melting and extruding the aforementioned polyester in an extruder into a film shape, cooling it on a rotary cooling drum, and then biaxially stretching the unstretched film. The biaxially stretched film can be obtained by sequentially biaxially stretching a longitudinally or transversely uniaxially stretched film in the transverse or longitudinal direction, or by simultaneously biaxially stretching an unstretched film in both the longitudinal and transverse directions.

[0054] In this invention, the stretching temperature during polyester film stretching is preferably set above the secondary transformation point (Tg) of the polyester. It is preferable to stretch the film by 1 to 8 times, particularly 2 to 6 times, in both the longitudinal and transverse directions.

[0055] The thickness of the aforementioned polyester film is preferably 12-50 μm, more preferably 15-38 μm, and even more preferably 19-33 μm. If the film thickness is 12 μm or more, it will not deform due to heat during film production, processing, or molding, which is preferable. On the other hand, if the film thickness is 50 μm or less, the amount of waste film after use will not increase drastically, which is preferable in terms of reducing environmental impact.

[0056] The aforementioned polyester film substrate can be a single layer or a multilayer consisting of two or more layers. For example, the substrate film can be a polyester film having a surface layer A that substantially does not contain particles with a particle size of 1.0 μm or larger and a surface layer B that contains particles. Preferably, surface layer A substantially does not contain inorganic particles with a particle size of 1.0 μm or larger.

[0057] In this method, surface layer A may contain particles with a diameter of less than 1.0 μm and greater than 1 nm. By substantially containing no particles with a diameter of 1.0 μm or greater, such as inorganic particles, surface layer A forms a smooth release layer surface, which reduces the possibility of defects caused by the transfer of particle shapes from the substrate onto the resin sheet.

[0058] In one approach, surface layer A, by not containing particles smaller than 1.0 μm, can more effectively suppress the transfer of particle shapes from the substrate to the resin sheet, thus preventing defects.

[0059] In one embodiment, the aforementioned polyester film substrate is preferably a laminated film having a surface layer A that is substantially free of inorganic particles on at least one side. This more effectively suppresses defects caused by the transfer of particle shapes from the substrate to the resin sheet. For example, the surface layer A, which is substantially free of particles with a particle size less than 1.0 μm, is preferably also substantially free of particles with a particle size greater than 1.0 μm.

[0060] In this invention, "substantially free of particles" means, for example, in the case of inorganic particles smaller than 1.0 μm, that the content is 50 ppm or less, preferably 10 ppm or less, and most preferably below the detection limit when quantifying inorganic elements by fluorescence X-ray analysis. This is because even without actively adding particles to the film, contaminants from foreign matter, raw material resins, or dirt adhering to the production line or equipment during the film manufacturing process can sometimes detach and mix into the film. Furthermore, "substantially free of particles with a diameter of 1.0 μm or larger" means actively free of particles with a diameter of 1.0 μm or larger.

[0061] In the case of a laminated polyester film consisting of two or more layers, it is preferable to have a surface layer B that can contain inorganic particles on the opposite side of the surface layer A, which is substantially free of inorganic particles.

[0062] As a laminated structure, if the layer on one side where the release layer is coated is designated as layer A, the layer on the opposite side is designated as layer B, and the remaining core layers are designated as layer C, then the layer configuration in the thickness direction can be a laminated structure such as release layer / A / B or release layer / A / C / B. Of course, layer C can also be composed of multiple layers. Furthermore, surface layer B may not contain inorganic particles. In this case, to impart slip properties for winding the film into a roll, it is preferable to provide a coating on surface layer B that contains at least inorganic particles and a binder.

[0063] In the polyester film substrate of the present invention, from the viewpoint of film slippage and ease of air expulsion, the surface layer B opposite to the side on which the release layer is formed preferably contains inorganic particles, and silica particles and / or calcium carbonate particles are particularly preferred. The content of inorganic particles in the surface layer B, in terms of the total amount of inorganic particles, is preferably 5,000 to 15,000 ppm.

[0064] At this point, the average surface roughness (Sa) of the thin film of surface layer B is preferably in the range of 1 to 40 nm. More preferably, it is in the range of 5 to 35 nm. When the total amount of silica particles and / or calcium carbonate particles is 5000 ppm or more and Sa is 1 nm or more, air can be uniformly discharged when the film is rolled into a roll, resulting in a good winding shape and good planarity, which is suitable for the manufacture of ultrathin ceramic green sheets. In addition, when the total amount of silica particles and / or calcium carbonate particles is 15000 ppm or less and Sa is 40 nm or less, lubricant aggregation is less likely to occur, and coarse protrusions cannot be formed. Therefore, the quality is stable during the manufacture of ultrathin ceramic green sheets, which is preferred.

[0065] In addition to silica and / or calcium carbonate, inactive inorganic particles and / or heat-resistant organic particles can be used as the particles contained in layer B. However, from the viewpoints of transparency and cost, silica particles and / or calcium carbonate particles are preferred. Other usable inorganic particles include alumina-silica composite oxide particles and hydroxyapatite particles. Heat-resistant organic particles include cross-linked polyacrylic acid particles, cross-linked polystyrene particles, and benzoguanamine particles. When using silica particles, porous colloidal silica is preferred. When using calcium carbonate particles, from the viewpoint of preventing lubricant detachment, light calcium carbonate with a surface treatment using a polyacrylic acid polymer is preferred.

[0066] The average particle size of the inorganic particles added to the surface layer B is preferably 0.1 μm or more and 2.0 μm or less, particularly preferably 0.5 μm or more and 1.0 μm or less. If the average particle size of the inorganic particles is 0.1 μm or more, the release film exhibits good sliding properties, which is preferred. Furthermore, if the average particle size is 2.0 μm or less, there is no concern about adverse effects on the smoothness of the release layer surface, and therefore no concern about pinholes forming on the ceramic green sheet, which is also preferred.

[0067] From the viewpoint of reducing pinholes, in order to prevent the mixing of inorganic particles such as lubricants, it is preferable not to use recycled materials in the layer on the side where the above-mentioned release layer is set, namely surface layer A.

[0068] The thickness ratio of surface layer A, which is the layer on the side where the above-mentioned release layer is provided, is preferably 20% or more and 50% or less of the total thickness of the substrate film. If it is 20% or more, it is less likely to be affected by particles contained in surface layer B, etc., from inside the film, and the average surface roughness Sa of the region is more likely to meet the above range, which is preferred. When it is 50% or less of the total thickness of the substrate film, the utilization rate of recycled materials in surface layer B can be increased, resulting in a low environmental impact, which is also preferred.

[0069] Furthermore, from an economic point of view, 50-90% by mass of film scraps and recycled plastic bottle materials can be used in layers other than surface layer A (surface layer B or the aforementioned intermediate layer C). In this case, the type, amount, particle size, and regional average surface roughness (Sa) of the lubricant contained in layer B preferably also meet the above-mentioned ranges.

[0070] In addition, in order to improve the adhesion of subsequent coatings such as release layers, or to prevent static electricity, a coating can be applied to the surface of surface layer A and / or surface layer B on the film before stretching or after uniaxial stretching in the film-making process, or corona treatment can be performed.

[0071] (release layer)

[0072] The release film of the present invention has a substrate and a release layer as described above, and the number of coarse protrusions on the surface of the release layer is adjusted in each range R1, R2, R3.

[0073] That is, when the roll is formed into a roll, the range from one end in the width direction to the center is defined as R1, the range from the center to both sides in the width direction is defined as R2, and the range from the other end in the width direction to the center is defined as R3. When the number of coarse protrusions with a height of 500 nm or more present on the surface of each range R1, R2, and R3 of the aforementioned release layer, as evaluated by the following method, is defined as A1, A2, and A3 respectively, the number of coarse protrusions shown in A1, A2, and A3 is 10 to 1000 per m respectively. 2 The range is calculated by X = ((A1+A3) / 2) / A2, where the ratio of coarse protrusions X is 0.2 to 5.0.

[0074] (Evaluation method for the number of large protrusions)

[0075] A resin layer for evaluation is coated onto the surface of the aforementioned release layer to form a composition with a dried thickness of 500 nm and then dried. The positions of pinholes in the resulting resin layer are marked. The height of the protrusions is measured with the surface of the aforementioned resin layer as a reference. The protrusion height is obtained by adding the thickness of the aforementioned resin layer (500 nm) to the obtained protrusion height. The number of coarse protrusions with a protrusion height of 500 nm or more is measured.

[0076] A release layer with such conditions is preferably formed by curing a composition containing silicone-based or long-chain alkyl resins. Without impairing the effects of the invention, in addition to the aforementioned resins and compounds, other components such as binders, crosslinking agents, adhesion promoters, and antistatic agents may be added.

[0077] (Adhesive components)

[0078] The binder component included in the release layer forming composition of the present invention is not particularly limited. However, in order to improve the crosslinking density, durability, and solvent resistance of the release layer, it is preferable to crosslink a component capable of crosslinking. Therefore, in the binder component, it is preferable to react a resin having reactive functional groups with a crosslinking agent. Furthermore, it is also preferable that either the reactive functional group or the crosslinking agent is self-crosslinked. However, in the present invention, it is not excluded that the binder component is composed solely of a resin having reactive functional groups or a crosslinking agent.

[0079] The resin having reactive functional groups is not particularly limited, and polyester resins, poly(meth)acrylic resins, polyurethane resins, polyolefin resins, epoxy resins, melamine resins, etc. are preferred. Among these resins, it is preferable that at least one of the following is selected as a reactive functional group: carboxyl, hydroxyl, epoxy, amino, etc.

[0080] Resins with reactive functional groups preferably have long-chain alkyl and / or organosilicon backbones in a portion of the resin backbone. By having a portion of the resin backbone containing long-chain alkyl and / or organosilicon backbones, which have low surface free energy, the compatibility of the organosilicon-based release agent and adhesive components (described later) becomes higher, reducing the likelihood of aggregation during drying and improving smoothness; therefore, this is preferred.

[0081] In the case of alkyd resins with long-chain alkyl side chains, the aforementioned acids with long-chain alkyl side chains (such as octanoic acid, stearic acid, etc.) can be mixed with polybasic acids such as phthalic acid, and then mixed with polyol components (such as pentaerythritol, diethylene glycol, etc.) to obtain the resin through a dehydration condensation reaction.

[0082] For example, a (meth)acrylic resin having long-chain alkyl groups can be included as an adhesive component, such as a (meth)acrylic resin having long-chain alkyl groups in its side chain.

[0083] (Meth)acrylate resins with long-chain alkyl side chains are preferably obtained by copolymerizing two or more (meth)acrylate monomers. As monomers for copolymerization, monomers having long-chain alkyl groups are preferably included (e.g., lauryl methacrylate, stearyl methacrylate, isodecyl methacrylate, etc.), and as reactive functional groups, monomers having hydroxyl groups are preferably included (e.g., hydroxyethyl methacrylate, hydroxypropyl methacrylate, hydroxybutyl methacrylate, etc.). In addition to the above, other known monomers such as methyl methacrylate, ethyl methacrylate, butyl methacrylate, hexanediol dimethacrylate, and butanediol diacrylate may be included to adjust the Tg of the resulting polymer, impart crosslinking properties, reactivity, etc.

[0084] The content of monomers having long-chain alkyl groups constituting the obtained acrylic resin is preferably 1 mol% or more and 50 mol% or less relative to all monomers constituting the acrylic resin. If it is 1 mol% or more, it has the effect of reducing surface free energy, and is therefore preferred. If it is 50 mol% or less, the content of monomers having reactive functional groups becomes relatively higher, and therefore the crosslinking density of the resin becomes higher, and is therefore preferred.

[0085] Specific examples of resins containing reactive functional groups, which have an organosilicon backbone in the resin matrix, include alkyd resins or acrylic resins having a polydimethylsiloxane backbone in the side chain. Commercially available examples include: SYMAC (registered trademark) US350, US352 (manufactured by Toa Synthetic Co., Ltd., reactive functional group: carboxyl group), SYMAC (registered trademark) US270 (manufactured by Toa Synthetic Co., Ltd., reactive functional group: hydroxyl group), etc.

[0086] In this invention, the release layer may contain melamine resin as a binder component.

[0087] For example, it may contain resins selected from all-ether methylated melamine resins, hydroxymethyl methylated melamine resins, and their polymers.

[0088] The preferred release layer contains a fully ether-type methylated melamine resin as an adhesive component. The fully ether-type methylated melamine resin is preferred in terms of low-temperature / short-time curing properties and adhesion to the polyester film. Commercially available examples include CYMEL 303LF and NIKALAC MW-30.

[0089] In one approach, the release layer may contain an alicyclic epoxy resin as a binder component. Examples of alicyclic epoxy resins include those manufactured by Daicel Corporation, trade names such as EHPE-3150, CEL2021P, and CEL2000.

[0090] In this invention, the adhesive component is contained in an amount of 55% to 95% by mass or more, preferably 60% to 90% by mass or more, relative to 100% by mass of the composition forming the release layer.

[0091] (Cross-linking agent)

[0092] The adhesive component preferably contains a crosslinking agent. There are no particular limitations on the crosslinking agent; melamine-based, isocyanate-based, carbodiimide-based, oxazoline-based, epoxy-based, etc., crosslinking agents can be used, and one or more can be used in combination. Crosslinking agents that react with reactive functional groups introduced into the adhesive component are particularly preferred.

[0093] From a reactivity point of view, melamine-based compounds are preferred as the crosslinking agent used in this invention. By using melamine-based compounds, even a coating weight of only 0.2 g / m² after the release layer has cured can be achieved. 2 The following types of films can also cure rapidly and have a higher crosslinking density, and are therefore preferred.

[0094] As the melamine-based compound used in this invention, any common substance can be used without particular limitation. Preferably, it is obtained by condensing melamine with formaldehyde, and each molecule contains one or more triazine rings, as well as hydroxymethyl and / or alkoxymethyl groups. Specifically, compounds obtained as follows are preferred: hydroxymethyl melamine derivatives obtained by condensing melamine with formaldehyde are subjected to a dehydration condensation reaction with lower alcohols such as methanol, ethanol, isopropanol, and butanol, followed by etherification. Examples of hydroxymethylated melamine derivatives include monomethylol melamine, dimethylol melamine, trimethylol melamine, tetramethylol melamine, pentamethylol melamine, and hexamethylol melamine. One or more of these derivatives may be used.

[0095] As melamine-based compounds, in order to increase the crosslinking density of the binder components, hexamethylol melamine, hexamethoxymethylol melamine, etc., which have multiple crosslinking sites in one molecule, are preferred. When using ether compounds obtained by dehydration condensation of alcohols in methylol melamine derivatives, from the viewpoint of reactivity, hexamethoxymethylol melamine obtained by dehydration condensation of methanol is particularly preferred.

[0096] The melamine used in this invention can also be a commercially available product. For example, CYMEL 300, CYMEL 301, CYMEL 303LF, CYMEL 350, CYMEL 370N, CYMEL 771, CYMEL 325, CYMEL 327, CYMEL 703, CYMEL 712, CYMEL 701, CYMEL 266, CYMEL 267, CYMEL 285, CYMEL 232, CYMEL235, CYMEL 236, CYMEL 238, CYMEL 272, CYMEL 212, CYMEL 253, CYMEL 254, CYMEL 202, CYMEL 207 (made by ALLNEX Japan Co., Ltd.), NIKALAC MW-30M, NIKALAC MW-30, NIKALAC MW-30HM, NIKALAC MW-390, NIKALAC MW-100LM, NIKALAC MX-750LM, NIKALAC MW-22, NIKALACMS-21, NIKALAC MS-11, NIKALAC MW-24X, NIKALAC MS-001, NIKALAC MX-002, NIKALAC MX-730, NIKALAC MX-750, NIKALAC MX-708, NIKALAC MX-706, NIKALAC MX-042, NIKALAC MX-035, NIKALAC MX-45, NIKALAC MX-43, NIKALAC MX-417, NIKALAC MX-410 (manufactured by Nippon Carbide Industries, Inc.), etc.

[0097] Among these, methylated melamine resins of the all-ether type are preferred in terms of low-temperature / short-time curing properties and adhesion to polyester films. Examples of commercially available products include CYMEL 303LF and NIKALAC MW-30.

[0098] In this invention, the amount of crosslinking agent contained in the adhesive component is preferably 15% by mass or more, more preferably 30% by mass or more, and even more preferably 50% by mass or more, relative to the resin having reactive functional groups. Furthermore, if the crosslinking agent can self-condense to form a resin film, the adhesive component may consist solely of the crosslinking agent. Containing 15% by mass or more of a crosslinking agent increases the crosslinking density of the release layer, thereby improving solvent resistance and elastic modulus, and is therefore preferred.

[0099] For example, in this invention, the crosslinking agent is contained in an amount of 5% by mass or more and 40% by mass or less relative to 100% by mass of the composition forming the release layer, preferably in an amount of 10% by mass or more and 40% by mass or less.

[0100] (catalyst)

[0101] The release layer forming composition of the present invention may also contain a catalyst to cure the crosslinking agent. When using melamine-based compounds, acid catalysts are preferred; however, there are no particular limitations, and carboxylic acid-based, metal salt-based, phosphate ester-based, and sulfonic acid-based catalysts are also preferred. Additionally, end-capped catalysts with acid sites capped may also be used. Particularly from a reactivity point of view, p-toluenesulfonic acid is preferred. When using isocyanate-based compounds, conventional compounds can be used, and organotin compounds, amine compounds, trialkylphosphine compounds, etc., are preferred. Furthermore, when the release layer is formed by a hydrosilylation reaction of an alkenyl polysiloxane and a hydrosilylated polysiloxane, a platinum catalyst can be used.

[0102] As a sulfonic acid catalyst, p-toluenesulfonic acid, xylenesulfonic acid, cumenesulfonic acid, dodecylbenzenesulfonic acid, dinonylnaphthalenesulfonic acid, trifluoromethanesulfonic acid, etc. can be preferred, and from the viewpoint of reactivity, p-toluenesulfonic acid can be particularly preferred.

[0103] Compared to other acid catalysts such as carboxylic acid catalysts, sulfonic acid catalysts have higher acidity and superior reactivity, thus enabling the processing of the release layer at lower temperatures. Therefore, they can suppress the reduction in film planarity and the deterioration of the wound appearance caused by heat during processing, making them preferred.

[0104] The sulfonic acid catalyst used in this invention can also be a commercially available product. Examples of commercially available products include Dryer 900 (p-toluenesulfonic acid, manufactured by Hitachi Chemical Co., Ltd.), NACURE DNNDSA series (dinonylnaphthalene disulfonic acid, manufactured by Kusunomoto Chemical Co., Ltd.), NACURE DNNSA series (dinonylnaphthalene (mono)sulfonic acid, manufactured by Kusunomoto Chemical Co., Ltd.), NACURE DDBSA series (dodecylbenzenesulfonic acid, manufactured by Kusunomoto Chemical Co., Ltd.), and NACURE p-TSA series (p-toluenesulfonic acid, manufactured by Kusunomoto Chemical Co., Ltd.).

[0105] The catalyst content is preferably 0.1 to 40% by mass relative to 100% by mass of the solid components of the composition forming the release layer. More preferably, it is 0.5 to 30% by mass. Even more preferably, it is 0.5 to 20% by mass. If 0.1% by mass or more, the curing reaction is easier to carry out, which is preferred. On the other hand, if it is 40% by mass or less, there is no concern about the migration of the acid catalyst to the ceramic green sheet to be formed, and no concern about adverse effects, which is therefore preferred. For example, the catalyst content can be 0.5 to 10% by mass.

[0106] (Silicone-based mold release agent)

[0107] The silicone-based release agent used in the release layer of this invention is a compound with an intramolecular silicone structure. There are no particular limitations as long as the effects of this invention are achieved; polyorganosiloxanes, etc., are suitable. Among polyorganosiloxanes, polydimethylsiloxane (PDMS) is preferred, and those containing functional groups in a portion of the PDMS are also preferred. Having functional groups facilitates intermolecular interactions such as hydrogen bonding with the binder resin and reduces migration to the ceramic green sheet, thus making it preferable.

[0108] The functional group introduced into polydimethylsiloxane is not particularly limited and can be either reactive or non-reactive. Furthermore, the functional group can be introduced into a single end, two ends, or side chain of the polydimethylsiloxane. Additionally, it can be introduced at one or multiple sites.

[0109] Examples of reactive functional groups introduced into polydimethylsiloxane include amino, epoxy, alicyclic epoxy, oxetyl, hydroxyl, mercapto, carboxyl, methacryloyl, and acryloyl groups. Examples of non-reactive functional groups include polyether, aralkyl, fluoroalkyl, long-chain alkyl, ester, amide, and phenyl groups. Theoretically, there should be no particular limitation, but those containing epoxy, carboxyl, polyether, methacryloyl, acryloyl, or ester groups are preferred.

[0110] The amount of silicone-based release agent relative to 100% by mass of the solid components of the composition forming the release layer is preferably 0.1 to 20% by mass, more preferably 0.2 to 15% by mass, and even more preferably 0.5 to 15% by mass. By including the silicone-based release agent in such an amount, it is possible to form 10 to 1000 coarse protrusions / m as shown in A1, A2, and A3, respectively. 2 The range of release films with a coarse protrusion ratio X[((A1+A3) / 2) / A2] of 0.2~5.0.

[0111] (Initiator)

[0112] When the adhesive components and silicone-based release agents have functional groups such as epoxy groups, alicyclic epoxy groups, and oxocyclic butyl groups, they can be cationicly cured using UV. An initiator can be used to perform this curing.

[0113] An acid-generating agent is preferably used as the initiator. There are no particular limitations on the acid-generating agent used; conventional acid-generating agents can be used. However, photo-acid-generating agents, which generate acid under active energy ray irradiation, are preferred because they can suppress heat during processing. While common acids such as sulfonic acids and carboxylic acids can also be used to obtain a release layer with high cross-linking density that can suppress the erosion of organic solvents, the high processing temperature required may result in a rough surface of the release layer due to thermal shrinkage of the original roll and a decrease in smoothness. Furthermore, metal salt-based, phosphate ester-based, and end-capped acid-generating agents with sealed acid sites can also be used. However, for the aforementioned reasons, from the viewpoint of heat during processing, photo-acid-generating agents are most preferred.

[0114] From a reactivity point of view, salts composed of ononium ions and non-nucleophilic anions are preferred as photoacid generators. Alternatively, organometallic complexes, such as iron-aromatic complexes, carbocation salts, such as zoonium, anthracene derivatives, and phenols substituted with electron-withdrawing groups, such as pentafluorophenol, can be used.

[0115] When using a salt composed of an onium ion and a non-nucleophilic anion as a photoacid-generating agent, for example, iodonium, sulfonium, or ammonium can be used as the onium ion. As the organic group of the onium ion, triaryl, diaryl (monoalkyl), monoaryl (dialkyl), or trialkyl groups can be used, and benzophenone or 9-fluorene can be introduced, or other organic groups can be used. As the non-nucleophilic anion, hexafluorophosphate, hexafluoroantimonate, hexafluoroborate, and tetra(pentafluorophenyl)borate are preferred. Additionally, tetra(pentafluorophenyl)gallium ions, anions in which some fluorine anions are replaced with perfluoroalkyl groups, or other anionic components can be used.

[0116] When using the aforementioned photoacid-generating agent, adding a sensitizer can also improve the reactivity of the polymerization reaction and further inhibit the erosion of the release layer caused by organic solvents. There are no particular limitations on the sensitizer; common sensitizers can be used, with anthracene derivatives and naphthalene derivatives being preferred. One or more sensitizers can be used.

[0117] The amount of photoacid-generating agent added to the coating liquid is preferably 0.1 to 10 parts by mass relative to the total mass of the binder a and release agent b, which are composed of cationic curing substances, contained in the release layer. More preferably, it is 0.5 to 8 parts by mass. Even more preferably, it is 1 to 5 parts by mass. Setting it to 0.1 parts by mass or more avoids concerns about insufficient acid production leading to inadequate curing, which is preferable. Furthermore, setting it to 10 parts by mass or less ensures that the amount of acid produced is appropriate, suppressing the migration of acid to the ceramic green sheet to be formed, which is also preferable.

[0118] The amount of sensitizer added relative to the photoacid generator is preferably 0.1 to 5 times by mass. More preferably, it is 0.1 to 2 times. If it is greater than 0.1 times, there is no concern about insufficient sensitization effect, which is preferred. If it is less than 5 times, there is no concern about hindering the absorption of the active energy rays of the photoacid generator and thus failing to generate sufficient acid, which is also preferred.

[0119] In this invention, additives such as adhesion improvers and antistatic agents can be added to the release layer without impairing its effects, but it is preferable that it does not contain particles. By ensuring that the release layer is free of particles, the deterioration of the smoothness of the release layer surface and the mixing of particles into the resin flakes caused by particle shedding can be suppressed. To improve adhesion to the substrate, the polyester film surface can also be pretreated with anchor coating, corona treatment, plasma treatment, atmospheric pressure plasma treatment, etc., before applying the release coating layer.

[0120] The release film of the present invention preferably has a release layer that is not easily charged. Regarding charge, more specifically, in the release film manufacturing process, when the film is wound up after the release layer is processed and stored in a roll, the increased charge over time can sometimes become a problem. For example, if the rolled film has a large charge, minute environmental foreign matter and film debris generated during slitting can easily adhere to the film in the slitting process and the ceramic green sheet forming process. Since these foreign matter adhering to the film may mix into the ceramic green sheet and cause defects, a release film with a release layer that is not easily charged is preferred.

[0121] As an example of evaluating the degree of resistance to charging, this can be confirmed by evaluating the charge on the release layer after it has been brought into contact with surface layer B, a load has been applied, and the contact time has been maintained. In this evaluation method, the increase in charge over time when the film is stored in a roll can be modeled and evaluated. Detailed evaluation methods will be described later.

[0122] The charge on the release layer, as measured by the evaluation method described later, is preferably ±5kV or less, for example, ±3.4kV or less, and more preferably ±3kV or less; the smaller the absolute value, the better. By ensuring the charge on the release layer is ±5kV or less, the increase in charge over time when the film is stored in a roll is minimal, and foreign matter is less likely to adhere to the film, thus this is preferred. The lower the charge on the release layer, the better; it can be 0.1kV or more, or 0.3kV or more.

[0123] The release film of the present invention may have a functional layer disposed between the substrate and the release layer. Examples of functional layers include antistatic layers and easily soluble resin layers, and there is no particular limitation.

[0124] By setting an antistatic layer, it is possible to prevent the adhesion of foreign objects caused by electric charge and suppress the charging during the peeling of ceramic green sheets, thus achieving stable peelability, and is therefore preferred.

[0125] By providing an easily soluble resin layer, the release layer formed on the surface of the release film can be easily separated and removed, and only the substrate film in which the residue of the release layer is absent or present can be recovered, which is therefore preferred.

[0126] For example, the release layer is substantially free of particles with a diameter greater than 1.0 μm. In this method, particles with a diameter less than 1.0 μm and greater than 1 nm may be present in the release layer. By making the release layer substantially free of inorganic particles with a diameter greater than 1.0 μm, pinholes in resin sheets, such as ceramic green sheets, which require high smoothness, can be suppressed, and resin sheets with uniform film thickness can be formed.

[0127] In one embodiment, the release layer preferably has high smoothness, and therefore the release layer of the present invention is preferably disposed on a substrate film having a surface layer A that is substantially free of inorganic particles, specifically substantially free of particles with a particle size of less than 1.0 μm, preferably a surface layer A that is substantially free of particles.

[0128] For example, a release layer that substantially does not contain particles smaller than 1.0 μm is preferably also substantially free of particles larger than 1.0 μm.

[0129] When a release layer is provided on a surface layer A that is substantially free of inorganic particles, the surface roughness (Sa) of the release layer region is 3.0 nm or less, and the maximum protrusion height (P) is 200 nm or less. For example, (Sa) can be 0.1 nm or more and 3.0 nm or less, and the maximum protrusion height (P) can be 1 nm or more and 200 nm or less; or (Sa) can be 0.2 nm or more and 3 nm or less, and the maximum protrusion height (P) can be 1 nm or more and 100 nm or less.

[0130] The maximum protrusion height (P) is preferably 1 nm or more and 50 nm or less, or it can be 1 nm or more and 40 nm or less. The maximum protrusion height (P) can be 1 nm or more and 35 nm or less.

[0131] By ensuring that the release layer meets these conditions, pinholes in the resin sheet of the film, such as ceramic green sheet, can be suppressed, and a resin sheet with uniform film thickness can be formed.

[0132] By keeping the surface roughness (Sa) and maximum protrusion height (P) of the release layer within such ranges, it is possible to form coarse protrusions of 10 to 1000 per m, as shown in A1, A2, and A3, respectively. 2 The range of release films with a coarse protrusion ratio X[((A1+A3) / 2) / A2] of 0.2~5.0.

[0133] In this invention, even if only the surface roughness (Sa) and maximum protrusion height (P) of the release layer are within the above range, it is not easy to derive the number of coarse protrusions and the ratio of coarse protrusions X shown in A1, A2 and A3. By comprehensively satisfying the various conditions described in this specification, conditions such as the ratio of coarse protrusions X can be derived.

[0134] By giving the release layer such characteristics, pinholes can be suppressed in resin sheets, such as ceramic green sheets, which require high smoothness, and resin sheets with uniform film thickness can be formed.

[0135] (Number of large protrusions)

[0136] In the release film roll, which is formed by winding the release film into a roll shape, the number of coarse protrusions with a height of 500 nm or more that are found on the surface of the aforementioned release layer in the range R1 of 100 mm from one end in the width direction to the center direction and the range R3 of 100 mm from the other end in the width direction to the center direction are designated as A1 and A3, respectively. Additionally, the number of coarse protrusions found in the range R2 of 50 mm from the center point in the width direction to the left and right sides is designated as A2 (center).

[0137] In this invention, the number of coarse protrusions shown in A1, A2, and A3 is 10 to 1000 per m, respectively. 2 Within the range, for example, 10~900 per m 2 The preferred range is 10 to 850 coarse protrusions / m². 2 The range is, for example, 10~700 pieces / m 2 The range can also be 20~700 pieces / m 2 The range.

[0138] By keeping the number of coarse protrusions within the aforementioned range, defects such as pinholes and sheet deformation can be suppressed when forming ceramic green sheets or resin sheets on the surface of the release layer. Furthermore, by including 10 protrusions / m... 2 The above protrusions can prevent the winding shape of the film roll from deteriorating, which is preferred.

[0139] In this invention, the ratio of coarse protrusions X[((A1+A3) / 2) / A2] in the release layer is 0.2 to 5.0. By keeping the ratio of coarse protrusions X within the above range, it is possible to obtain a state in which there is no deviation or very little deviation in the number of coarse protrusions in the film width direction.

[0140] For example, when used as a film for process applications, it can maintain a state where there is no deviation or minimal deviation in the number of coarse protrusions in the width direction of the release film. Therefore, there is no deviation in the number of coarse protrusions in the entire release film, and for ceramic green sheets with a thickness of approximately 0.2 μm to 1.0 μm, the generation of pinholes can be further reduced. In addition, the risk of pinhole generation in ceramic green sheets and the like can be reduced. Furthermore, the defect rate of resin sheets such as ceramic green sheets can be reduced, and waste can be decreased.

[0141] The ratio X of the number of coarse protrusions shown in [((A1+A3) / 2) / A2] is, for example, in the range of 0.4 to 2.5, or in the range of 0.4 to 2.10, or in the range of 0.7 to 1.5.

[0142] Here, when the ratio of coarse protrusions X is less than 0.2, there is a tendency for the number of coarse protrusions A2 (center) identified in a range R2 extending 50 mm to the left and right from the center point in the film width direction to be excessively greater than the number of coarse protrusions A1 and A3 near the film ends. As a result, air release is poor, winding performance deteriorates, the film is prone to becoming charged, and foreign objects are easily trapped.

[0143] (Evaluation method for the number of large protrusions)

[0144] The evaluation method for the number of coarse protrusions can be calculated as follows: A resin layer composition for evaluation is coated onto the surface of the release layer to a dried thickness of 500 nm and dried. The number of pinholes in the resulting resin layer is measured and marked. The height of the protrusions is measured using a VertScan (registered trademark) at a multiplier of 50. The protrusion height is calculated by adding the resin layer thickness of 500 nm to the obtained protrusion height. Examples of resin layer compositions used for evaluation include those described in the embodiments.

[0145] Figure 1 This is a schematic diagram illustrating the height of the large protrusions in this invention. For example, it shows how the large protrusions 40 protrude from the surface of the substrate 10 toward the release layer 20 in a release film having a film substrate 10 and a release layer 20 in sequence.

[0146] In the above-described method for evaluating coarse protrusions, a resin layer 30 is formed, the number of pinholes in the resulting resin layer is measured and marked, and the height of the protrusion is determined using a VertScan (registered trademark) at a magnification of 50x. The measured protrusion height at this point is equivalent to... Figure 1 The protrusion height was measured at 41. Next, the protrusion height was calculated by adding the resin layer thickness of 500 nm to the obtained protrusion height. Figure 1 The actual height of the protrusion is 42.

[0147] In this invention, the number of coarse protrusions with a height of 500 nm or more existing on the surface of the release layer can be calculated as follows. It should be noted that the resin layer used in evaluating the number of coarse protrusions in this invention can be formed using the same composition and conditions as the resin sheet in this invention.

[0148] (Thickness of the release layer)

[0149] The thickness of the release layer in this invention is not particularly limited, but is preferably 30 nm or more. More preferably, it is 50 nm or more, and even more preferably 100 nm or more. A thickness of 30 nm or more ensures sufficient peelability, allowing for defect-free peeling of the ceramic green sheet. Furthermore, a thickness of 30 nm or more allows for the filling of protrusions in the polyester film substrate, improving smoothness. The upper limit of the release layer thickness is not particularly limited, but is preferably 1000 nm or less. It can also be 800 nm or less, or 500 nm or less. In particular, a thickness of 800 nm or less ensures sufficient coatability of the release layer forming composition, preventing groove-like streaks caused by coating from remaining on the coating surface and reducing the smoothness of the release layer. Additionally, it eliminates the need to reduce the linear speed during release layer processing to suppress streak formation, thus improving productivity, which is preferable.

[0150] (Method for manufacturing release film)

[0151] In this invention, the coating of the release layer forming composition that forms the release layer is preferably carried out online during the manufacturing process of the polyester film or offline after the manufacturing of the polyester film.

[0152] When coating is performed online, the following method is preferred: a coating liquid containing a release resin is applied to a film that has been stretched along the film flow direction (longitudinal) and uniaxially oriented, and then stretched transversely (in a direction orthogonal to the film flow direction) to form a release layer while achieving biaxial orientation.

[0153] When coating is performed offline, the following method is used: a coating solution containing a release resin is applied to one side of a biaxially oriented polyester film, the solvent is removed by drying, and then the film is dried by heating, heat curing, or UV curing.

[0154] When applying coatings online, water-based coatings are preferred. There are no particular limitations on the type of water-based coating, but the addition of water-soluble organic solvents, such as alcohols, is preferred.

[0155] There are no particular limitations on the coating solution used when coating offline, but organic solvents are preferred, and solvents with a boiling point of 90°C or higher are even more preferred. By adding a solvent with a boiling point of 90°C or higher, it is possible to prevent sudden boiling during drying, promote coating leveling, and improve the smoothness of the dried coating surface.

[0156] As for the coating method of the aforementioned release layer forming composition, any known coating method can be applied, such as roll coating methods such as gravure coating and reverse coating, bar coating methods such as wire rod coating, mold coating, spray coating, air knife coating, etc.

[0157] In this invention, the release film utilizes a roll-to-roll conveying method during the processing of the release layer and the hydrophobic layer. Therefore, after the processing of the release layer and the hydrophobic layer, the release film is wound into a roll and stored. Furthermore, the molding and peeling of the resin sheet are also performed using a roll-to-roll method.

[0158] The tension when winding the release film into a roll is preferably 10 N / m to 300 N / m. A winding tension of 10 N / m or higher is preferred as it prevents winding misalignment. Furthermore, it prevents unwinding during storage in a roll, eliminating concerns about scratches entering the release layer or increased charge on the roll. A winding tension of 300 N / m or lower is preferred as it prevents deformation or adhesion of the release film due to tight winding.

[0159] When winding the release film into a roll, a contact roller is preferably used. The contact pressure of the contact roller is preferably 100~3000 N / m. If it is 100 N / m or more, it can reduce the accompanying air mixed in during winding and suppress the occurrence of winding misalignment, which is preferred. If it is 3000 N / m or less, it can suppress the deformation of the release film caused by the pressure of the contact roller and obtain a release film with excellent planarity, which is also preferred.

[0160] (Heat curing process)

[0161] The heat curing process is not particularly limited, and any known drying oven can be used. Regarding the type of drying oven, it can be either roller-supported or suspended. The heat curing process can be continuous with the initial drying process or discontinuous; from a productivity point of view, a continuous process is preferred.

[0162] The temperature for the heat curing process is preferably 80°C or higher and 180°C or lower, more preferably 90°C or higher and 160°C or lower, and most preferably 90°C or higher and 140°C or lower. At temperatures below 180°C, the planarity of the film can be maintained, minimizing the possibility of uneven thickness in the ceramic green sheets, which is preferred. At temperatures below 140°C, processing can be performed without compromising the planarity of the film, further reducing the possibility of uneven thickness in the ceramic green sheets, making this particularly preferred. At temperatures above 80°C, curing is sufficiently achieved in the case of thermosetting resins, which is also preferred.

[0163] The time for the heat curing process is preferably 2 seconds or more and 30 seconds or less, more preferably 2 seconds or more and 20 seconds or less. If the time is 2 seconds or more, the curing of the thermosetting resin will take place, which is preferred. In addition, if the time is 30 seconds or less, the flatness of the film caused by heat will not decrease, which is also preferred.

[0164] In the heat curing process of the present invention, for example, by using multiple drying ovens, the number of coarse protrusions and the ratio X of the number of coarse protrusions can be guided to a specified range.

[0165] The following is an example of a drying process, but the present invention is not limited to this method.

[0166] (Initial drying process)

[0167] An initial drying oven (first drying oven) can also be used. The internal pressure difference (first drying oven chamber pressure - cleaning tunnel pressure) of the initial drying oven (first drying oven) is preferably positive. The internal pressure difference is preferably 10~40 Pa, more preferably 15~30 Pa. Setting it to 10 Pa or more can suppress air from flowing from the coating section into the drying oven, thus maintaining good cleanliness within the drying oven, which is therefore preferable. Furthermore, setting it to 40 Pa or less can prevent solvent evaporation caused by high-temperature air flowing out of the drying oven to the coating section. Additionally, the possibility of contaminants generated by paint volatilization within the drying oven flowing out to the coating section is reduced, thus suppressing particulate deterioration.

[0168] (Final drying oven)

[0169] Following the initial drying oven (first drying oven), a final drying oven is installed for the heat curing process. For example, the internal pressure difference of the final drying oven (final drying oven internal pressure - cleaning tunnel pressure) is preferably positive. The internal pressure difference is preferably 10~40 Pa, more preferably 15~30 Pa. Setting it to 10 Pa or more prevents air from flowing into the drying oven from the oven outlet (winding chamber), thus maintaining good cleanliness within the drying oven, which is therefore preferable. Furthermore, setting it to 40 Pa or less prevents air from the final drying oven from flowing out into the winding chamber, thus preventing airflow and the resulting dust and particle agitation, which is also preferable.

[0170] (The second drying process and thereafter)

[0171] For example, one or more drying ovens can be installed between the initial drying oven (first drying oven) and the final drying oven. Such drying ovens are referred to, for example, as the second drying process and thereafter. For example, the internal pressure difference (drying oven internal pressure - cleaning tunnel pressure) of the drying ovens in the second drying process and thereafter is preferably positive pressure. The internal pressure difference is preferably 10 to 40 Pa. More preferably, it is 15 to 30 Pa. By setting it to 10 Pa or more, it is possible to suppress the inflow of air from the drying oven outlet (winding chamber) into the drying oven, thus maintaining the cleanliness inside the drying oven well, which is therefore preferred. In addition, by setting it to 40 Pa or less, it is possible to prevent air from the final drying oven from flowing out into the winding chamber, which would cause airflow and dust to be stirred up, resulting in the rise of particles, which is also preferred.

[0172] In one embodiment, the gas pressure in the initial drying process is preferably within 10 Pa of the gas pressure in the final drying oven. This allows for more effective guidance of the ratio X of coarse protrusions within the range of this invention, reducing fluctuations in the number of protrusions on the film surface in the width direction.

[0173] (Active energy ray irradiation process)

[0174] The active energy rays used in this invention can be any known technology such as ultraviolet light or electron beams. The cumulative irradiation dose of the active energy rays can be expressed as the product of illuminance and irradiation time. For example, in the case of ultraviolet light, a dose of 20 to 500 mJ / cm² is preferred. 2 In the case of an electron beam, the preferred value is approximately 0.1 to 40 kGy. By setting it above the aforementioned lower limit, the release layer can be fully cured, therefore it is preferred. By setting it below the aforementioned upper limit, thermal damage to the film caused by heat during irradiation can be suppressed, and planarity can be maintained, therefore it is preferred.

[0175] When irradiating a thin film with active energy rays, it is preferable to use a support roller to hold the back side of the film. By providing a support roller, the distance to the active energy ray source can be kept constant, thus enabling uniform irradiation, which is preferable. Furthermore, it is preferable to irradiate the film while simultaneously cooling the surface of the support roller. By cooling, the film is less susceptible to heat-induced damage even during irradiation with active energy rays, maintaining its planarity, which is also preferable.

[0176] The release film obtained by the present invention is preferably rolled into a roll after passing through a heat curing process and / or an active energy ray curing process. The time from the end of the heat curing process or the active energy ray curing process until the film is rolled into a roll is preferably 2 seconds or more, more preferably 3 seconds or more. If it is 2 seconds or more, the release film whose temperature has risen during the heat curing process or the active energy ray irradiation process is cooled and rolled onto the roller, so the flatness will not deteriorate, which is preferred.

[0177] The release film obtained by this invention can undergo various treatments during the period from the time it is rolled into a roll after the heating and curing process, such as static removal treatment, corona treatment, plasma treatment, ultraviolet irradiation treatment, electron beam irradiation treatment, etc.

[0178] (particle)

[0179] In the manufacturing process of the release film, a particle meter can be used to manage the cleanliness of the processing area. The particle meter can measure dust particles larger than 0.5 μm, preferably 300 particles / CF or less, more preferably 250 particles / CF or less, and even more preferably 200 particles / CF or less. By setting it to 300 particles / CF or less, it is possible to reduce the amount of dust entering the release layer and adhering to the release layer, thereby reducing the number of protrusions on the surface of the release layer of the resulting release film.

[0180] The desired number of dust particles larger than 0.5μm is less, for example, 5 or more per CF, or even 10 or more per CF.

[0181] Methods for reducing particulate matter include cleaning the cleanroom containing the processing equipment and cleaning the rollers of the processing equipment. Processing with a very low and stable particulate count is preferred, as it reduces the number of protrusions on the surface of the release layer caused by external interference foreign matter entering the release layer and adhering to / entering onto the surface of the release layer.

[0182] (Resin sheet)

[0183] In one embodiment, the release film of the present invention is not particularly limited to any resin sheet and can be applied to the manufacture of adhesives and optical films. In another embodiment, it is a release film for molding resin sheets containing an inorganic compound. Examples of inorganic compounds include metal particles, metal oxides, minerals, etc., such as calcium carbonate, silica particles, aluminum particles, barium titanate particles, etc.

[0184] Examples of resins include polyvinyl acetal resin and poly(meth)acrylate resin.

[0185] The present invention has a release layer with high smoothness and a back layer with excellent smoothness, operability and antistatic properties. Therefore, even if the resin sheet contains these inorganic compounds, it is possible to suppress the defects that may be caused by inorganic compounds, such as resin sheet breakage and difficulty in peeling the resin sheet from the release layer.

[0186] The resin components used to form resin sheets can be selected appropriately based on their intended use.

[0187] In one embodiment, the resin sheet containing the inorganic compound is a ceramic green sheet. For example, the ceramic green sheet may contain barium titanate as the inorganic compound. In another embodiment, the thickness of the resin sheet is 0.2 μm or more and 1.0 μm or less.

[0188] (Ceramic green sheets and ceramic capacitors)

[0189] Typically, a multilayer ceramic capacitor has a cuboid ceramic blank. Inside the ceramic blank, a first internal electrode and a second internal electrode are alternately arranged along the thickness direction. The first internal electrode is exposed at a first end face of the ceramic blank. A first external electrode is disposed on the first end face. The first internal electrode is electrically connected to the first external electrode at the first end face. The second internal electrode is exposed at a second end face of the ceramic blank. A second external electrode is disposed on the second end face. The second internal electrode is electrically connected to the second external electrode at the second end face.

[0190] In one embodiment, the release film of the present invention is a release film for manufacturing ceramic green sheets, used to manufacture such laminated ceramic capacitors.

[0191] For example, the method for manufacturing ceramic green sheets using the release film for manufacturing ceramic green sheets of the present invention can form ceramic green sheets with a thickness of 0.2 μm to 1.0 μm.

[0192] More specifically, for example, ceramic green sheets are manufactured as follows: First, using the release film of the present invention as a carrier film, a ceramic slurry for forming a ceramic green body is coated and dried. The ceramic green sheet is required to be extremely thin, with a thickness of 0.2 to 1.0 μm. A conductive layer for forming a first or second internal electrode is printed on the coated and dried ceramic green sheet. The ceramic green sheet, the ceramic green sheet with the conductive layer for forming the first internal electrode printed on it, and the ceramic green sheet with the conductive layer for forming the second internal electrode printed on it are appropriately stacked and pressed to obtain a master laminate. The master laminate is divided into multiple parts to produce unprocessed ceramic green bodies. A ceramic green body is obtained by firing the unprocessed ceramic green body. Then, by forming the first and second external electrodes, a multilayer ceramic capacitor can be completed.

[0193] Example

[0194] The present invention will now be described in more detail using examples, but the invention is not limited to these examples. The characteristic values ​​used in the present invention are evaluated using the methods described below.

[0195] (Determination of film width)

[0196] Using a measuring instrument (measuring tape), measure the length from one end of the film in the width direction (TD direction) to the other end, and use the obtained value as the film width.

[0197] (Thickness measurement)

[0198] The cut release films were embedded in resin and then ultrathinly sliced ​​using an ultramicrotome. Cross-sectional observation was then performed using a JEM2100 transmission electron microscope (TEM), and the film thickness of the release layer was determined from the observed TEM images.

[0199] (Evaluation of the number of large protrusions)

[0200] R1 is defined as a 100mm range from one end of the roll-shaped release film in the width direction toward the center, R2 is defined as a 50mm range from the center to both sides in the width direction, and R3 is defined as a 100mm range from the other end in the width direction toward the center. The number of coarse protrusions in each range R1, R2, and R3 is evaluated.

[0201] Specifically, solvent (ethanol / toluene = 50 / 50:mass ratio) was added to polyvinyl acetal resin (S-LEC BM-S manufactured by Sekisui Chemicals Co., Ltd.) to achieve a solid content of 10.0% by mass. Using a spreader, the resulting material was coated onto the surface of the release layer of a release film to achieve a dried thickness of 500 nm. The coating was dried at 90°C for 1 minute to obtain a resin sheet. This resin sheet was then molded onto the release film. The locations of pinholes visible within a 10cm × 10cm area on the resin sheet surface were marked. The height of the protrusions was measured using a VertScan (registered trademark) multiplied by 50. The actual protrusion height was obtained by adding the measured protrusion to the resin sheet thickness of 500 nm; measurements exceeding 500 nm were considered protrusions. Furthermore, 10 measurements were performed at different locations, and the average value was converted to 1m. 2 The value is used as the number of protrusions.

[0202] (Measurement conditions)

[0203] • Measurement mode: WAVE mode

[0204] Objective lens: 50x

[0205] · 0.5× Tube lens

[0206] • Measurement area: 187μm × 139μm

[0207] (Analysis conditions)

[0208] • Surface calibration: 4 calibrations

[0209] • Interpolation processing: Full interpolation

[0210] (Average surface roughness Sa, maximum protrusion height P)

[0211] The measurements were performed using a VertScan (registered trademark) R550H-M100 under the following conditions. The average surface roughness (Sa) and maximum protrusion height (P) of the area were obtained by averaging the results of 36 measurements, after removing the 7 points with the largest values ​​(including the maximum) and the 4 points with the smallest values ​​(including the minimum).

[0212] (Measurement conditions)

[0213] • Measurement mode: WAVE mode

[0214] Objective lens: 50x

[0215] · 0.5× Tube lens

[0216] • Measurement area: 187μm × 139μm

[0217] (Analysis conditions)

[0218] • Surface calibration: 4 calibrations

[0219] • Interpolation processing: Full interpolation

[0220] (Evaluation of the peelability of ceramic raw shards)

[0221] The composition consisting of the following materials was stirred and mixed, and dispersed in a bead mill with 0.5 mm diameter zirconia beads at 2500 rpm for 15 minutes to obtain a ceramic slurry.

[0222] 30.1 parts by weight of toluene

[0223] 26.2 parts by weight of ethanol

[0224] Barium titanate (HPBT-1 manufactured by Fuji Titanium Co., Ltd.) 38.5 parts by weight

[0225] Polyvinyl butyral (S-LEC BM-S, manufactured by Sekisui Chemicals Co., Ltd.) 3.2 parts by weight

[0226] DOP (dioctyl phthalate) 0.6 parts by weight

[0227] Next, using an applicator, the dried slurry was applied to the release surface of the obtained release film sample to a thickness of 3 μm. After drying at 90°C for 1 minute, the ceramic green sheet was formed on the release film. The release film with the ceramic green sheet was then de-electrified using a de-electrode (KEYENCE CORPORATION, SJ-F020). Peeling was then performed at a width of 30 mm, a peel angle of 90 degrees, and a peel speed of 10 m / min. The stress applied during peeling was measured as the peel force.

[0228] (with battery power)

[0229] Prepare two evaluation samples, each cut into 10cm x 10cm pieces from the release film. Use a destaticator (KEYENCE CORPORATION, SJ-F020) to destaticate the two samples. After confirming a voltage of 0kV, place the release layer with the release layer facing upwards into contact with surface layer B. Clamp the two samples together with protective paper and apply a 10.2kg load (10kPa pressure) to them, maintaining the temperature at 50°C for 48 hours. After 48 hours, allow the temperature to return to room temperature (25°C), then peel off the two samples. Measure the charge on the release layer in contact with surface layer B using a digital electrostatic potential meter (KSD-1000, Kasuga Electric Co., Ltd.). Evaluate the charge measured at this point according to the following criteria.

[0230] ◎: The absolute value of the charge is less than 3kV

[0231] ○: The absolute value of the charge is above 3kV and below 5kV

[0232] ×: The absolute value of the charge exceeds 5kV.

[0233] (Preparation of polyethylene terephthalate granules (PET(I)))

[0234] As the esterification reactor, a continuous esterification reactor consisting of a stirring device, a condenser, and three fully mixed tanks with a raw material inlet and a product outlet is used. The TPA (terephthalic acid) flow rate is set at 2 tons / hour, the EG (ethylene glycol) ratio is set at 2 moles per 1 mole of TPA, and the antimony trioxide ratio is set at 160 ppm per scalp of Sb atoms relative to the generated PET. These slurries are continuously fed to the first esterification reactor of the esterification reactor, and the reaction is carried out at atmospheric pressure with an average residence time of 4 hours and a temperature of 255°C. Next, the reaction product from the first esterification reactor was continuously removed from the system and fed to the second esterification reactor. EG removed by distillation from the first esterification reactor was added to the second esterification reactor at a mass ratio of 8% relative to the generated PET. Further additions were made of EG solution containing 65 ppm of magnesium acetate tetrahydrate relative to the generated PET and 40 ppm of TMPA (trimethyl phosphate) relative to the generated PET. The reaction was carried out at atmospheric pressure, with an average residence time of 1 hour, and at 260°C. Then, the reaction product from the second esterification reactor was continuously removed from the system and fed to the third esterification reactor. The reaction was carried out using a high-pressure disperser (manufactured by Nippon Seiki Co., Ltd.) at 39 MPa (400 kg / cm²). 2 0.2% by mass of porous colloidal silica with an average particle size of 0.9 μm, obtained by dispersion treatment with an average of 5 passes under pressure, and 0.4% by mass of synthetic calcium carbonate with an average particle size of 0.6 μm and 1% by mass of ammonium salt of polyacrylic acid attached relative to calcium carbonate, were respectively prepared into 10% EG slurry. The slurry was added gradually while reacting at 260°C under normal pressure with an average residence time of 0.5 hours. The esterification reaction product generated in the third esterification reactor was continuously fed to a three-stage continuous polycondensation reactor for polycondensation. After filtration through a filter made of 95% stainless steel fiber with a cutoff diameter of 20 μm, the product was ultrafiltered and extruded into water. After cooling, it was cut into small flakes to obtain PET flakes (hereinafter referred to as PET(I)) with an intrinsic viscosity of 0.60 dl / g. The lubricant content in the PET flakes was 0.6% by mass.

[0235] (Preparation of polyethylene terephthalate granules (PET(II)))

[0236] On the other hand, in the manufacture of the above-mentioned PET(I) flakes, PET flakes with an intrinsic viscosity of 0.62 dl / g that are completely free of particles such as calcium carbonate and silica are obtained (hereinafter referred to as PET(II)).

[0237] (Manufacturing of laminated thin film F1)

[0238] After drying, these PET flakes were melted at 285°C and then melted again at 290°C using a separate melt extruder. This process involved two stages of filtration: a filter made of sintered stainless steel fibers with a cutoff diameter of 15 μm and a filter made of sintered stainless steel particles with a cutoff diameter of 15 μm. The filters were then combined in the feed head and layered with PET(I) as surface layer B (reverse demolding side layer) and PET(II) as surface layer A (demolding side layer). The layers were extruded (cast) into sheets at a speed of 45 m / min and electrostatically bonded / cooled on a casting drum at 30°C using an electrostatic sealing method to obtain unstretched polyethylene terephthalate sheets with an intrinsic viscosity of 0.59 dl / g. The layer ratio was adjusted based on the discharge rate of each extruder, resulting in PET(I) / (II) = 60% by mass / 40% by mass. Next, the unstretched sheet was heated in an infrared heater and then stretched 3.5 times longitudinally using the speed difference between the rollers at a roller temperature of 80°C. It was then fed into a tenter frame and stretched 4.2 times transversely at 140°C. Following this, it was heat-treated at 210°C in a heat-setting zone. Then, it underwent a 2.3% relaxation treatment at 170°C transversely to obtain a biaxially stretched polyethylene terephthalate film F1 with a thickness of 31 μm. The surface layer A of the obtained film F1 has a Sa value of 2 nm, and the surface layer B has a Sa value of 28 nm.

[0239] (Laminated thin film F2)

[0240] As the laminated film F2, A4100 (Cosmoshine (registered trademark), manufactured by Toyobo Co., Ltd.) with a thickness of 25 μm is used. A4100 is configured such that it is substantially free of particles, but a coating containing particles is formed on the surface layer B side by in-line coating. The surface layer A of the laminated film F2 has a thickness Sa of 1 nm, and the surface layer B has a thickness Sa of 2 nm.

[0241] (Laminated thin film F3)

[0242] As the laminated film F3, E5101 (TOYOBOESTER (registered trademark) film, manufactured by Toyobo Co., Ltd.) with a thickness of 25 μm is used. E5101 is configured to contain particles in surface layer A and surface layer B. The Sa of surface layer A and surface layer B of the laminated film F3 is 24 nm.

[0243] (Resin solution a) Acrylic resin containing long-chain alkyl groups

[0244] The mixture was prepared in a ratio of 20 mol% stearate (meth)acrylate, 40 mol% hydroxyethyl (meth)acrylate, and 40 mol% methyl (meth)acrylate. The mixture was diluted with toluene to a solids concentration of 40% by mass. Then, 0.5 mol% azobisisobutyronitrile (AIBN) was added under a nitrogen atmosphere and copolymerized to obtain resin solution A. The weight-average molecular weight of the resulting polymer was 30,000.

[0245] (Example 1)

[0246] (Preparation of release coating liquid)

[0247] Acrylic resin (a), melamine resin (manufactured by Nippon Carbide Industries, Inc., NIKALAC MW-30M) as a crosslinking agent (b), silicone release agent (polyether-modified polydimethylsiloxane manufactured by Momentive, TSF4446, 100% solids content) as a curing catalyst (dryer#900 manufactured by Hitachi Chemical Polymer Co., Ltd.), and solvent (MEK / toluene / n-heptane = 50 / 30 / 20: mass ratio) were added to make the solids content 5.0% by mass to obtain the release coating liquid.

[0248] (Formation of the release layer)

[0249] The obtained coating solution was passed through a filter capable of removing more than 99% of foreign matter larger than 0.5 μm. Then, using a reverse gravure printing plate, it was coated onto the laminated film F1 (350 mm wide) with a dried release layer thickness of 200 nm. The fan speed and internal pressure of the drying oven were set as described in Table 1, and the film was dried at 140°C for 15 seconds to obtain the release film. The particle count in the roll-out / wrap-up sections is shown in Table 1.

[0250] (Examples 2, 3, 4, and 5)

[0251] Adjust the concentration of solid components in the coating liquid to change the thickness of the dried release layer to the values ​​recorded in Table 1. Otherwise, form the release layer using the same steps as in Example 1.

[0252] (Example 6)

[0253] The silicone-based release agent was changed to (single-terminal carboxyl-modified polydimethylsiloxane, X22-3710, 100% solids, manufactured by Shin-Etsu Chemical Industry Co., Ltd., with alkyl groups sandwiched between the dimethylsiloxane and the carboxyl group), and the release layer was formed by the same steps as in Example 1.

[0254] (Examples 7 and 8)

[0255] The circulating fan speed and internal pressure of the first drying oven are changed to those recorded in Table 1. Otherwise, the release layer is formed by the same steps as in Example 1.

[0256] (Example 9)

[0257] Using the mixing amounts listed in Table 1, a release layer coating liquid was prepared with a solid content concentration of 12.5% ​​by mass for the following components: melamine-based compound (all-ether methylated melamine, 100% solid content, manufactured by Sanwa Chemical Industry Co., Ltd., trade name MW-30M, weight-average degree of polymerization 1.3), silicone release agent (single-terminal carboxyl-modified polydimethylsiloxane, X22-3710, 100% solid content, manufactured by Shin-Etsu Chemical Industry Co., Ltd., with an alkyl group sandwiched between the dimethylsiloxane and the carboxyl group), acid catalyst (p-toluenesulfonic acid, manufactured by Hitachi Chemical Co., Ltd., trade name Dryer (registered trademark) 900, 50% solid content), and solvent (MEK / toluene = 50 / 50: mass ratio). Using this release layer coating liquid, a release layer was formed through the same steps as in Example 1.

[0258] (Example 10)

[0259] Using the mixing amounts listed in Table 1, the following components were mixed: 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexane carboxylic acid ester (product name: CELLOXIDE (registered trademark) 2021P, manufactured by Daicel Corporation, 100% by weight of solids, 2 functional groups); release agent b: polydimethylsiloxane containing alicyclic epoxy groups (product name: UV Poly215, manufactured by Arakawa Chemical Industry Co., Ltd., 100% by weight of solids); and acid-generating agent: 0.26 parts by weight of boron-based cationic curing UV catalyst (product name: UV...). A release layer coating solution was prepared by mixing CATA211 (19% by mass of active ingredient, manufactured by Arakawa Chemical Industry Co., Ltd.) and a solvent (MEK / toluene = 50 / 50: mass ratio) with a solid content concentration of 5.0% by mass. Similar to Example 1, the resulting coating solution was passed through a filter and coated onto the laminated film F1 using a reverse gravure printing press to achieve a release layer thickness of 200 nm after drying. After drying at 90°C for 15 seconds, the film was irradiated with a UV lamp (Heraeus, H bulb) with a cumulative light intensity of 100 mJ / cm². 2 UV curing is performed using ultraviolet light, and a release layer is formed using the same steps as in Example 1.

[0260] (Example 11)

[0261] The substrate width of the laminated film F1 is changed to 250 mm. Otherwise, a release layer is formed by the same steps as in Example 1.

[0262] (Example 12)

[0263] The substrate width of the laminated film F1 is changed to 450 mm, and otherwise a release layer is formed by the same steps as in Example 1.

[0264] (Example 13)

[0265] The substrate width of the laminated film F1 is changed to 800 mm, and otherwise a release layer is formed by the same steps as in Example 1.

[0266] (Example 14)

[0267] The substrate width of the laminated film F1 was changed to 1400 mm, and a release layer was formed according to the same steps as in Example 1. After manufacturing the release film, the film was cut into 3 strips of 450 mm each using a slit, and then evaluated.

[0268] (Example 15)

[0269] The laminated film is changed to F2, except that a release layer is formed by the same steps as in Example 1.

[0270] (Example 16)

[0271] Before the demolding process, polyester powder is removed from the surface of the film-coated part using a microfiber film cleaning cloth. Otherwise, a release layer is formed by the same steps as in Example 1.

[0272] (Comparative Example 1)

[0273] The laminated film was changed to F3, and coating was performed on the surface layer A side. Otherwise, the release layer was formed using the same steps as in Example 1. The result was that, due to the high surface roughness of the coated surface, the release layer surface had a large number of protrusions.

[0274] (Comparative Example 2)

[0275] The rotational speed of the circulating fan was changed to that shown in Table 1, and the release layer was formed using the same steps as in Example 1. The result was that the internal pressure balance changed due to the change in the circulating fan speed, leading to a significant deterioration in the particle count and a higher number of protrusions on the surface of the release layer.

[0276] (Comparative Example 3)

[0277] For the coating liquid used in Example 9, the coating liquid described in Table 1 without the addition of silicone release agent was used for coating, except that the release layer was formed by the same steps as in Example 9. The result was a high number of protrusions on the surface of the release layer. It was considered that the resulting release film roll was prone to becoming charged, and dust could easily enter.

[0278] (Comparative Example 4)

[0279] Polyester powder is collected on the surface of the film using a microfiber film cleaning cloth and sprinkled onto the end of another polyester film for release coating. Otherwise, a release layer is formed by the same steps as in Example 1.

[0280] (See Example 1 for reference)

[0281] The solids concentration of the coating liquid described in Example 9 was adjusted, and the thickness of the dried release layer was changed to that described in Table 1. The high solids content of the coating liquid resulted in a high-viscosity coating liquid, causing streaks on the surface of the release layer obtained under the coating conditions described in Example 1. Therefore, to obtain sufficient leveling time, the linear velocity was reduced to two-thirds. Otherwise, the release layer was formed using the same steps as in Example 9. Because the release layer was thicker, protrusions and dust on the substrate coating surface were firmly embedded within it, resulting in a significantly lower number of protrusions on the release layer surface. On the other hand, the need to slow down the linear velocity reduced productivity.

[0282] (Example 17)

[0283] To confirm the stability of the processing conditions, continuous processing was performed under the conditions of Example 1, and the performance of samples processed two days after the start of processing was evaluated. The processing conditions remained unchanged, but processing was conducted under slightly higher particle levels in the processing area. Furthermore, the number of protrusions on the surface of the release layer was confirmed to be stable.

[0284] Various compositions, film-forming conditions, and physical properties of the embodiments and comparative examples are shown in Tables 1 to 3.

[0285] [Table 1]

[0286]

[0287] [Table 2]

[0288]

[0289] [Table 3]

[0290]

[0291] The release film of the present invention is a release film in which the number of protrusions on the surface of the release layer and the distribution of protrusions in the width direction are controlled. Furthermore, the present invention can provide a release film that can be defectively coated with resin sheets to form a slurry without deteriorating the rollability of the release film, and in particular, can defectively form ceramic green sheets.

[0292] On the other hand, the number of coarse protrusions in Comparative Examples 1-4 exceeded 1000 per m. 2 Pinholes may occur during the manufacturing of ceramic green sheets, etc.

[0293] Furthermore, the ratio X of coarse protrusions in Comparative Example 4 is outside the scope of this invention; the number of protrusions near the ends of the film is high, and the distribution of coarse protrusions is uneven. Therefore, it is necessary to use the area near the center of the release film, resulting in more waste film compared to this invention.

[0294] Industrial availability

[0295] According to the present invention, a release film having a release layer on one side of a substrate film and having excellent peelability / smoothness is provided, which can be manufactured without concern about defects such as the formation of thin resin sheets.

[0296] Explanation of reference numerals in the attached figures

[0297] 10 Thin film substrates

[0298] 20 release layers

[0299] 30 resin layers

[0300] 40. Large protrusions

[0301] 41. Measuring the height of the protrusion

[0302] 42 Actual protrusion height

Claims

1. A release film having a substrate and a release layer, wherein the substrate is a polyester film with a width of 200-900 mm, wherein... R1 is defined as a 100mm area from one end in the width direction to the center when the roll is formed into a roll; R2 is defined as a 50mm area from the center to both sides in the width direction; R3 is defined as a 100mm area from the other end in the width direction to the center; and A1, A2, and A3 are defined as the number of coarse protrusions with a height of 500nm or more present on the surface of each range R1, R2, and R3 of the release layer, as evaluated by the following method. The number of coarse protrusions shown in A1, A2, and A3 are 10~1000 per m, respectively. 2 Scope The ratio of coarse protrusions, X, calculated using X = ((A1 + A3) / 2) / A2, is 0.2 to 5.

0. Evaluation method for the number of coarse protrusions: A resin layer for evaluation is coated onto the surface of the release layer to form a composition with a dried thickness of 500 nm and then dried. The positions of pinholes in the resulting resin layer are marked. The height of the protrusions is measured with the surface of the resin layer as a reference. The protrusion height is obtained by adding the thickness of the resin layer (500 nm) to the obtained protrusion height. The number of coarse protrusions with a protrusion height of 500 nm or more is measured.

2. The release film according to claim 1, wherein, The average surface roughness (Sa) of the release layer surface is below 3.0 nm, and the maximum protrusion height (Rp) is below 200 nm.

3. The release film according to claim 1, wherein, The thickness of the release layer is less than 800 nm.

4. The release film according to claim 1, wherein, The release film is a release film used for manufacturing ceramic green sheets or resin sheets.

Citation Information

Patent Citations

  • Mold release film

    JP2007237497A

  • Method of manufacturing biaxially oriented polyester film

    JP2009012242A

  • Oriented polyester film roll and method for manufacturing oriented polyester film roll

    JP2022159254A